Simon Hantaï - Ault, Julie 1957-; Crowner, Sarah 1974-; Odita, Odili Donald 1966-; Quinlan, Eileen 1972-; Reed, David 1946-; Schoolwerth, Pieter 1970-; Siena, James 1957- (ER Publishing, 2021)
ER Publishing first launches a book collection titled TRANSATLANTIQUE dedicated to artist writings and their invaluable perspectives. Each book is devoted to an American or European artist active primarily in the second half of the 20th century. All the contributions are from artists living on the other side of the Atlantic. They add their perspectives to the critical discussion on the featured artist's practice. Each book is edited by a Guest Editor who is an important actor of the art world and has a great knowledge of the featured artist. Simon Hantaï (1922-2008) was a painter born in Hungary. He moved to France in 1948. He is considered as a major figure of the abstract painting. He produced a complex and multiple work marked starting 1960 by the use of "folding as a method
Keywords: Hantaï, Simon -- 1922-2008